Did China's dual-credit policy promote innovation in new energy vehicle enterprises? An empirical study based on the PSM-DID method - Sun, Jianguo; Tian, Mingfu (Frontiers in Environmental Economics, 2023)
Introduction Based on the microdata of 36 A-share new energy vehicle (NEV) enterprises from 2015 to 2021, this study empirically investigates whether the introduction of the double credit policy (DCP) promoted the innovation of NEV enterprises. Methods The propensity score matching difference-in-differences (PSM-DID) method was used. Results The following results were found. First, the introduction of the DCP inhibits the innovation of NEV enterprises. However, as the DCP stabilizes, the inhibitory effect gradually decreases and shows a tendency to turn into a facilitating effect. Second, the DCP affects the innovation output of enterprises by influencing their research and development (R&D) investment. R&D investment has a mediating role in the DCP, affecting the innovation of new energy vehicle enterprises. Third, at the firm level, the inhibitory effect of the DCP is more evident in non-state-owned enterprises (non-SOE) and insignificant for state-owned enterprises (SOE), while at the regional level, the inhibitory effect of the DCP is more evident for non-eastern regions and insignificant for eastern regions. Discussion This study finds the inhibitory effect of the implementation of the DCP on the innovation of NEV enterprises and have potential guiding significance for the future formulation of NEV market development policies and the promotion of high-quality development of the NEV industry.